Performance prediction of the coherent radar detector on measured UAVs data - Rosamilia, Massimo; Aubry, Augusto; Balleri, Alessio; Carotenuto, Vincenzo; De Maio, Antonio (Institution of Engineering and Technology (IET), 2022)
This paper presents measurements of Radar Cross Section (RCS) of five Unmanned Aerial Vehicles (UAVs), comprising both consumer grade and professional small drones, collected in a semi-controlled environment as a function of azimuth aspect angle, polarization and frequency in the range 8.2-18 GHz. A first-order statistical analysis of the measured RCSs is firstly reported prior to assessing the radar detection performance on both measured and bespoke simulated data (leveraging the results of the developed statistical analysis), including, as benchmark terms, the curves for non-fluctuating and Rayleigh fluctuating targets.
Keywords: radar cross section; measured data; statistical analysis; radar detection performance; drone detection